المنهج الدعوي عند الإمام محمد بن عبد الله الخليلي من خلال المراسلات : دراسة تحليلية - ريامي، محمد خميس مرهون (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This study sheds light on milestones of the thought and method of da'wah in Imam Mohammed Al-khalili's correspondence. The study uses the inductive, historical, and analytic approaches in order to derive preaching contents and examines the most important features of the preaching thought and the Imam's efforts in the educational, religious, moral and intellectual areas through analysis of correspondence. The study also undertakes an examination into the source of Da'wah that are the Holy Qur'an and the Sunnah of the Prophet Mohammed, in addition to ijtihad and experiences of reform leaders in order to deduce the Imam's educational approach in faith and moral. This is achieved by looking at the practical aspects of the Islamic unity project, through its communication with scholars, leaders, kings, and leaders of reform in the Islamic world as well the Imam's fatwas and with women's issues. The most important outcome of the study is that it is able to identify the strengths and weaknesses of the preaching approach of the Imam. The Imam's approach appears to be relating to a religious reform, building humans who are able to contribute to civilization. The study proposes that it is crucial to explore and search for correspondence of Imam's Al-khalili as many of them are still inaccessible because of being in private libraries.